Willensfreiheit - Keil, Geert (De Gruyter, 2022)
This book surveys recent debates on freedom of will, incorporating the implications of modern brain research. The author develops an original, capability-based conception of freedom of will. Geert Keil proposes that the well-understood capability for deciding one way or another is reconcilable with the findings of empirical science, but not with the metaphysical doctrine of determinism.